The imperial temptation : the new world order and America's purpose - Tucker, Robert W. (Council on Foreign Relations Books, 1992)
With communism in retreat following the sudden end of the cold war, America's brand of democracy appeared triumphant around the world. Yet, paradoxically, the United States was left floundering for a new global agenda. In this critical analysis of American foreign policy priorities, Robert W. Tucker and David C. Hendrickson argue that the Bush administration, in its attempts to address the challenges posed by the new global realities, has betrayed the fundamental ideals on which this country was founded. Taking the gulf war as their starting point, Tucker and Hendrickson dissect President Bush's vision of a new world order, exposing its inconsistency with America's traditional diplomatic principles. They criticize Bush's all-out military assault on Iraq as a disproportionate and inhumane response to the crisis